2013
DOI: 10.1111/ctr.12163
|View full text |Cite
|
Sign up to set email alerts
|

Impaired exercise capacity after lung transplantation is related to delayed recovery of muscle strength

Abstract: Lung transplant recipients report reduced exercise capacity despite satisfactory graft function. We analysed changes in lung function, six-min walk distance (6MWD), and quadriceps strength in the first 26-wk post-transplant and examined what factors predict 6MWD recovery. All lung transplant recipients at a single institution between June 2007 and January 2011 were considered for inclusion. Lung function, 6MWD, and quadriceps strength corrected for body weight (QS%) were recorded pre- and two-, six-, 13-, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
3
34
2
3
Order By: Relevance
“…A similar degree of muscle atrophy of the rectus femoris has been reported in people with COPD using ultrasound and of the plantarflexors using magnetic resonance imaging (MRI) . Quadriceps strength of individuals with advanced ILD in our cohort was 77% of predicted, which is similar to previous studies in individuals with advanced ILD and lung transplant candidates with other diagnoses . Although quadriceps strength has been the main focus in characterizing peripheral muscle weakness in individuals with advanced lung disease, the distal lower limb muscles, which are key muscles for walking and balance, have not been explored in ILD.…”
Section: Discussionsupporting
confidence: 85%
“…A similar degree of muscle atrophy of the rectus femoris has been reported in people with COPD using ultrasound and of the plantarflexors using magnetic resonance imaging (MRI) . Quadriceps strength of individuals with advanced ILD in our cohort was 77% of predicted, which is similar to previous studies in individuals with advanced ILD and lung transplant candidates with other diagnoses . Although quadriceps strength has been the main focus in characterizing peripheral muscle weakness in individuals with advanced lung disease, the distal lower limb muscles, which are key muscles for walking and balance, have not been explored in ILD.…”
Section: Discussionsupporting
confidence: 85%
“…with poor post-transplantation outcomes in liver and renal transplant recipients (6,7), therefore, we hypothesize that it may negatively impact survival following LTx. Previous studies on sarcopenia have focused on physical activity and rehabilitation in LTx patients, and the quadriceps muscle is mainly used in the context of skeletal muscle assessment (3,(30)(31)(32). Thoracic muscles and major respiratory muscles have been surgically dissected; nevertheless, sarcopenia of thoracic muscles in LTx patients has not been fully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation protocols of the analyzed studies (lung function, QoL, exercise capacity and quadriceps force) were similar to other studies in different patients (11,12,15,16) . Recent study (32) showed that the delay in the recovery of the exercise capacity after lung transplant is not associated with the delay in the improvement of the function of the transplanted organ but it results to the slow recovery of the muscular force. Thus, the authors reinforce the necessity of clinical trials to a better comprehension about the influence of the physical activity in the improvement of the exercise capacity after lung transplant.…”
Section: Discussionmentioning
confidence: 99%